2016
DOI: 10.4081/mi.2016.6806
|View full text |Cite
|
Sign up to set email alerts
|

Mental health literacy among undergraduate students of a Saudi tertiary institution: a cross-sectional study

Abstract: The issue of mental health literacy has been widely studied in developed countries, with few studies conducted in Arab countries. In this study we aimed to investigate mental health literacy and attitudes towards psychiatric patients among students of Jazan University, Kingdom of Saudi Arabia. A crosssectional study was conducted among undergraduate students using a validated Arabicversion questionnaire. A total of 557 students were recruited from different Jazan university colleges. The majority of students (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 9 publications
5
24
1
2
Order By: Relevance
“…Thus, the attitude of the participants could be considered mixed according to each item analysis in the BMI tool. The study results are consistent with a study that was conducted with a similarly aged population in Saudi Arabia [ 14 ]. Among 575 undergraduate students, it was found that they reported a mixed attitude toward people with mental illness, with 32% reporting that they could not maintain a friendship with a person who has a mental illness and 82.5% reporting that people deserve the same rights as anyone else [ 14 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Thus, the attitude of the participants could be considered mixed according to each item analysis in the BMI tool. The study results are consistent with a study that was conducted with a similarly aged population in Saudi Arabia [ 14 ]. Among 575 undergraduate students, it was found that they reported a mixed attitude toward people with mental illness, with 32% reporting that they could not maintain a friendship with a person who has a mental illness and 82.5% reporting that people deserve the same rights as anyone else [ 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…The study results are consistent with a study that was conducted with a similarly aged population in Saudi Arabia [ 14 ]. Among 575 undergraduate students, it was found that they reported a mixed attitude toward people with mental illness, with 32% reporting that they could not maintain a friendship with a person who has a mental illness and 82.5% reporting that people deserve the same rights as anyone else [ 14 ]. Moreover, 66.5% of 650 Saudi adults aged > 18 years old reported negative attitudes toward people with mental illness concerning treatment, work, marriage, and recovery, and toward getting professional help [ 1 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations